Macroeconomic principles and problems a pluralist introduction - Schneider, Geoffrey Eugene (Routledge pluralist introductions to economics, 2023)
Macroeconomic Principles and Problems: A Pluralist Introduction offers a comprehensive overview of the major topics in modern macroeconomics, from mainstream and heterodox perspectives. This textbook examines the key macroeconomic problems and policy debates facing contemporary society, including economic crises, sustainability, fiscal and monetary policy, government debt, state-led vs. market-led approaches for growth, and unregulated trade vs. protectionism. Written in an engaging style and focused on real-world examples, this textbook brings macroeconomics to life. Multiple examples of how each economic model works, coupled with critical analysis of the assumptions behind them, enable students to develop a sophisticated understanding of the material. Digital supplements are also available for students and instructors. Macroeconomic Principles and Problems offers the most contemporary and complete package for any pluralist macroeconomics class"--